Clicktivism: A Systematic Heuristic. Issue 2 (June 2014) - Halupka, Max
<x xml:space="preserve">Abstract</x> This article argues that clicktivism is a legitimate political act. It emphasizes that such acts, through a recurrent negative discourse, have been marginalized. As a result, new modes of participation that draw upon the simplification of social connectivity have largely been ignored in the mainstream Political Science literature. In addressing this issue, the article develops a heuristic that identifies seven dimensions (or characteristics) of clicktivism. This new heuristic will allow for the analysis of clicktivism as a form of civic engagement separate from digital activism more broadly. Subsequently, the article applies the heuristic to several popular forms of clicktivism, including social buttons and the creation of memes, demonstrating both its utility and flexibility.